Lecture Transformation in Modern Higher Education - G. I. Ibragimov; A. A. Kalimullina (Высшее образование в России, 2022)
The relevance of the topic stems from the contradiction between the experience accumulated by higher school in adapting lecture as a form of organization of education to the new conditions of education functioning and the insufficient attention of researchers to analyzing this experience. The purpose of the study was to identify the role, place and directions of the lecture transformation in modern higher education. To achieve it, a meta-analysis of publications on the topic over the past ten years was carried out (2011–2021). In total, 52 scientific articles published in peer-reviewed leading domestic pedagogical journals and other scientific and methodological publications were analyzed. The selection of articles for analysis was carried out by the presence of the keyword “lecture” in the article title.The results of the study show that despite the wide variety and general availability of information and communication sources the lecture cannot be supplanted in the system of higher education, but new demands have been placed on it, as its role in the system of higher education changes. The authors have identified the main requirements for a modern lecture, namely problem setting, structure flexibility, focus on dialogic forms of communication with students, effective feedback. The leading trend in the development of lectures in a modern university is a combination of scientific character, information value and high professionalism inherited from traditional lectures with dialogue and a variety of lecture types, an increase in interactivity to enhance the educational and communication activities of students. It has been established that the transformation of a lecture in modern higher education goes in the following directions: organizational-content, functional-structural, and communication. The authors dwell on the content of each direction and propose prospective areas for further research.